Develop the Competitive Advantage from Resources Based View RBV: Case Study on the Commercial Agencies of the Telecoms Sector in Algeria (Revue El-Wahat pour les Recherches et les Etudes, 2022)
We aim through this study mainly to measure the relationship between the RBV and competitive advantage through its components. We have followed an induction and experimental approach. Where we have developed a model that shows the relationship between the variables (Organization resources and competitive advantage). In this study, we depended on basic resources in the soft power era and the dominant of intangible resources versus material resources, such as human capital, organizational capital, technological capital, relationships and the reputation of the organization. This study was conducted on a sample of 149 individuals from 32 telecom commercial agencies in Algeria, where the main results of this study showed the existence of a (strong - positive) correlation and effectiveness of RBV and the competitive advantage.Key words- Resources based view, Tangible resources, Intangible resources, Competitive advantage, Telecom sector.